Evolving Accelerated Amidation by SpyTag/SpyCatcher to Analyze Membrane Dynamics. Issue 52 (5th December 2017) - Keeble, Anthony H.; Banerjee, Anusuya; Ferla, Matteo P.; Reddington, Samuel C.; Anuar, Irsyad N. A. Khairil; Howarth, Mark
Abstract: SpyTag is a peptide that forms a spontaneous amide bond with its protein partner SpyCatcher. This protein superglue is a broadly useful tool for molecular assembly, locking together biological building blocks efficiently and irreversibly in diverse architectures. We initially developed SpyTag and SpyCatcher by rational design, through splitting a domain from a Gram‐positive bacterial adhesin. In this work, we established a phage‐display platform to select for specific amidation, leading to an order of magnitude acceleration for interaction of the SpyTag002 variant with the SpyCatcher002 variant. We show that the 002 pair bonds rapidly under a wide range of conditions and at either protein terminus. SpyCatcher002 was fused to an intimin derived from enterohemorrhagic Escherichia coli . SpyTag002 reaction enabled specific and covalent decoration of intimin for live cell fluorescent imaging of the dynamics of the bacterial outer membrane as cells divide. Abstract : Unnatural Selection : The spontaneously reactive SpyTag/SpyCatcher pair was previously developed by engineering an adhesin protein from S. pyogenes . Phage library selection enabled evolution of the peptide and protein partners for accelerated isopeptide bond formation with high specificity. The resulting SpyCatcher002 was fused to the protein intimin on the bacterial outer membrane, thereby allowing fluorescent imaging of intimin dynamics during cell division.